Low Antituberculosis Drug Concentrations in HIV-Tuberculosis-Coinfected Adults with Low Body Weight: Is It Time To Update Dosing Guidelines? - Sekaggya-Wiltshire, Christine; Chirehwa, Maxwell; Musaazi, Joseph; von Braun, Amrei; Buzibye, Allan; Muller, Daniel; Gutteck, Ursula; Motta, Ilaria; Calcagno, Andrea; Fehr, Jan S; Kambugu, Andrew; Castelnuovo, Barbara; et al. (Antimicrobial agents and chemotherapy, 2019)
Antituberculosis drugs display large pharmacokinetic variability, which may be influenced by several factors, including body size, genetic differences, and drug-drug interactions. We set out to determine these factors, quantify their effect, and determine the dose adjustments necessary for optimal drug concentrations. HIV-infected Ugandan adults with pulmonary tuberculosis treated according to international weight-based dosing guidelines underwent pharmacokinetic sampling (1, 2, and 4 h after drug intake) 2, 8, and 24 weeks after treatment initiation. Between May 2013 and November 2015, we enrolled 268 patients (148 males) with a median weight of 53.5 (interquartile range [IQR], 47.5 to 59.0) kg and a median age of 35 (IQR, 29 to 40) years. Population pharmacokinetic modeling was used to interpret the data and revealed that patients weighing <55 kg achieved lower concentrations than those in higher weight bands for all drugs in the regimen. The models predicted that this imbalance could be solved with a dose increment of one fixed-dose combination (FDC) tablet for the weight bands of 30 to 37 and 38 to 54 kg. Additionally, the concomitant use of efavirenz increased isoniazid clearance by 24.1%, while bioavailability and absorption of rifampin and isoniazid varied up to 30% in patients on different formulations. Current dosing guidelines lead to lower drug exposure in patients in the lower weight bands. Simply adding one FDC tablet to current weight band-based dosing would address these differences in exposure and possibly improve outcomes. Lower isoniazid exposures due to efavirenz deserve further attention, as does the quality of currently used drug formulations of anti-TB drugs. (This study has been registered at ClinicalTrials.gov under identifier NCT01782950.).